Commentary: Academia: A Poetic Memoir (LEARNing Landscapes, 2010)
A sociological maxim is that one sees from a particular position. As my position in academia changed, I saw differently. In this piece, I offer brief descriptions of my experience in four positions—Untenured Professor, Tenured Associate Professor, Full Professor and Professor Emeritus—and illustrate those with poems written during each of those positions.
Keywords: academia; poetry; postion